Epigenetic silencing of IRF1 dysregulates type III interferon responses to respiratory virus infection in epithelial to mesenchymal transition - Yang, Jun; Tian, Bing; Sun, Hong; Garofalo, Roberto P.; Brasier, Allan R. (Nature microbiology, 2017)
Chronic oxidative injury produced by airway disease triggers a transforming growth factor-β (TGF-β)-mediated epigenetic reprogramming known as the epithelial–mesenchymal transition (EMT). We observe that EMT silences protective mucosal interferon (IFN)-I and III production associated with enhanced rhinovirus (RV) and respiratory syncytial virus (RSV) replication. Mesenchymal transitioned cells are defective in inducible interferon regulatory factor 1 (IRF1) expression by occluding RelA and IRF3 access to the promoter. IRF1 is necessary for the expression of type III IFNs (IFNLs 1 and 2/3). Induced by the EMT, zinc finger E-box binding homeobox 1 (ZEB1) binds and silences IRF1 . Ectopic ZEB1 is sufficient for IRF1 silencing, whereas ZEB1 knockdown partially restores IRF1-IFNL upregulation. ZEB1 silences IRF1 through the catalytic activity of the enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), forming repressive H3K27(me3) marks. We observe that IRF1 expression is mediated by ZEB1 de-repression, and our study demonstrates how airway remodelling/fibrosis is associated with a defective mucosal antiviral response through ZEB1-initiated epigenetic silencing. This study explores the mechanism for enhanced respiratory virus replication in airway epithelial cells subject to mesenchymal reprogramming, implicating a role for epigenetic silencing interferon pathways.